REALIZATION OF THE RIGHT TO PENSION PROVISION FOR FORMER MILITARY AND LAW ENFORCEMENT OFFICERS: ISSUES OF THEORY AND PRACTICE - Makeieva, Olena; Tyubay, Anastasiya (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to study the theoretical and practical problems of realization of the right to pension provision for former military personnel and retired law enforcement officers. Research methods: general scientific methods: induction, deduction, documentary analysis, synthesis, comparative analysis, generalization. Results: the article analyzes the legislation regulating pensions for former military personnel and retired law enforcement officers, identifies the regulatory procedure for recalculation of pensions, changes that will guarantee the execution of a court decision by the authorized bodies, and reveals the procedure for restoring the violated right in court. Discussion: the author points to the inaction of the authorized body; and notes that despite the existence of a clear regulatory procedure for the recalculation of pensions, the authorized bodies do not fulfill their obligations; despite the positive case law, plaintiffs are forced to prove their right to pension benefits. The problem of adequate pension provision in Ukraine is relevant, as it includes all categories of people. However, among all categories, we believe the most problematic is the pension provision for former military personnel and retired law enforcement officers. Despite the existence of a clear regulatory procedure for the recalculation of pensions, the authorized bodies do not fulfill their obligations. This leads to the need to defend the rights guaranteed by the Constitution of Ukraine in court. Despite the positive case law, plaintiffs are forced to take active steps to ensure that the Pension Fund of Ukraine begins to comply with the court decision.